2000
DOI: 10.1016/s1074-5521(00)00135-6
|View full text |Cite
|
Sign up to set email alerts
|

d -Ala– d -X ligases: evaluation of d -alanyl phosphate intermediate by MIX, PIX and rapid quench studies

Abstract: These three approaches support the rapid (more than 1000 min(-1)), reversible formation of the enzyme intermediate D-Ala(1)-P by members of the D-Ala-D-X (where X is Ala, Ser or Lac) ligase superfamily.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 43 publications
1
13
1
Order By: Relevance
“…A number of poly(amino acids) such as folyl‐poly γ‐glutamate play roles in the housekeeping functions of their producer cells and like the muramyl peptide chains, the tripeptide glutathione or the d ‐Ala‐ d ‐Ala dipeptides of the bacterial cell walls are formed by amino‐acid ligases such as UDP‐ N ‐acetyl‐muramoyl‐ l ‐alanine‐glutamate ligase, glutathione synthetase or d ‐Ala‐ d ‐Ala ligase [37]. They condense carboxylate‐containing compounds via the intermediacy of acylphosphates as in the case of formation of the d ‐Ala‐ d ‐Ala dipeptide [38]. Remarkably, in several compounds synthesized by this mechanism, unusual peptide bonds sych as the γ‐glutamyl peptide bond also occur as in the muramyl peptides and glutathione.…”
Section: Discussionmentioning
confidence: 99%
“…A number of poly(amino acids) such as folyl‐poly γ‐glutamate play roles in the housekeeping functions of their producer cells and like the muramyl peptide chains, the tripeptide glutathione or the d ‐Ala‐ d ‐Ala dipeptides of the bacterial cell walls are formed by amino‐acid ligases such as UDP‐ N ‐acetyl‐muramoyl‐ l ‐alanine‐glutamate ligase, glutathione synthetase or d ‐Ala‐ d ‐Ala ligase [37]. They condense carboxylate‐containing compounds via the intermediacy of acylphosphates as in the case of formation of the d ‐Ala‐ d ‐Ala dipeptide [38]. Remarkably, in several compounds synthesized by this mechanism, unusual peptide bonds sych as the γ‐glutamyl peptide bond also occur as in the muramyl peptides and glutathione.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for the formation of this intermediate has been determined from positional isotope exchange studies which have shown that a labeled oxygen atom from the carboxylic acid is transferred to the inorganic phosphate product (Figure 5). [47-53] The existence of the acylphosphate intermediate is also supported by diazomethane trapping studies on carbamoyl phosphate synthetase which trapped the reactive intermediate, carboxyphosphate. [54] Formation of an acylphosphate intermediate has been implicated by the discovery of highly potent mechanistic inhibitors of DDLigase which mimic the reaction of a nucleophile with this phosphorylated intermediate (see the section 6 for additional details).…”
Section: Mechanismmentioning
confidence: 99%
“…The reaction starts with the attack on the first D-Ala by the g-phosphate of ATP, to give an acylphosphate. This is followed by an attack by the amino group of the second D-Ala to yield a tetrahedral intermediate, which collapses into D-Ala-D-Ala and P i (Mullins et al, 1990;Healy et al, 2000b). In this respect, the mechanism is similar to that of the Mur ligases (see 'Biosynthesis of the UDP-MurNAcpeptides').…”
Section: Formation Of D-ala -D-alamentioning
confidence: 99%